A new questionnaire for measuring quality of life - the Stark QoL. Issue 1 (December 2015) - Hardt, Jochen
Abstract Objective The Stark questionnaire measures health-related quality of life (QoL) using pictures almost exclusively. It is supplemented by a minimum of words. It comprises a mental and a physical health component. Methods A German sample of n = 500 subjects, age and gender stratified, filled out the Stark Qol questionnaire along with various other questionnaires via internet. Results The physical component shows good reliability (Cronbach's alpha = McDonalds Omega = greatest lower bound = .93), the mental component can be improved (Cronbach's alpha = .63, McDonalds Omega = .72, greatest lower bound = .77). Confirmatory factor analysis shows a good fit (Bentlers CFI = .97). Construct validity was proven. Conclusion The Stark QoL is a promising new development in measuring QoL, it is a short and easy to apply questionnaire. Additionally, it is particularly promising for international research.